想像與現實的交織：設計領域想像-創造歷程之建構 Weaving Imagination into Reality: Imagination-Creativity Process in Design Domain - 王佳琪 Chia-Chi Wang; 何曉琪 Hsiao-Chi Ho (National Taiwan Normal University, 2021)
本研究旨在探討大學設計類科教師指導學生進行設計創作時，從點子的發想到最終產品的過程中，如何連結自身想像力與創造力之歷程。研究參與者為指導學生參加國內外設計競賽多次獲獎的五名得獎績優大學教師，以及九位受指導並獲獎的學生為對象。資料蒐集以半結構訪談並採三角檢驗、研究成員檢核會議等提升研究效度。研究結果發現，當學生進行設計創作時，在不斷地發散與收斂思考的交互作用下，其自身想像力與創造力的連結，共歷經四個階段。首先為發想與分析階段，此階段為探尋設計的點子來源，學生考量相關競賽徵稿、在地特色、社會議題、傳統文化等面向梳理可行的設計主題，教師透過對話引導學生思考主題的價值。第二個階段是產生與修正階段，主要是設計點子修改與討論，教師透過創意發想、換位思考等策略引導學生檢驗點子是否呼應設計初衷、商品實用性、業界需求。第三個階段是實作與評估階段，是進行點子原型的製作，在考量功能實用與美觀性、製作成本考量材質、使用者經驗下製作點子原型。最後，進入溝通與最佳化階段，教師帶領學生考量市場需求與相關競賽需求，產出一個成熟的作品。在未來建議上，本研究試圖提出設計教育規劃的核心重點，以作為未來創新教育推展之參考。 This study explored the transformation of imagination and creativity from an initial idea into a final product in the design domain. Five award-winning university teachers, who have supervised award-winning students in domestic and foreign design competitions, and their nine students participated. Data collection consisted of interviews, which were coded verbatim, with the teachers and students, and triangulation and member checks were used to validate the study. The results indicated that the design process is based on the interaction of imagination and creativity. This imagination-creativity process involves the transformation of initial ideas to the final product in four stages: (1) the idea and analysis stage; (2) generation and modification stage; (3) implementation and evaluation stage; and (4) communication and optimization stage. The idea and analysis stage focuses on idea generation. Teachers guide students in considering the value of ideas through discussion of topics including relevant competition, local needs, social issues, and traditional culture. In the generation and modification stage, teachers employ creative-thinking strategies to instruct students to examine their ideas and possible products and industrial demands to modify design ideas. In the implementation and evaluation stage, students create a prototype of their ideas based on the practicality, aesthetics, costs, materials of the final product and user experience. In the communication and optimization stage, teachers lead students in producing a well-designed product to meet the needs of marketing and design competition. Suggestions for design and innovation in education are proposed.